(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2023)
An important task of social policy in the EU countries is to overcome poverty, reduce risk social groups due to effective social, economic, psychological help and support, providing decent living conditions, etc. Material and living conditions are one of the most important factors in determining the indicators of the population’s standard of living. Poor material and living conditions, stratification of the population by income level and quality of life, lack of adequate social assistance to families with low-income levels, families with several children, families with dependent children with disabilities, leads to various social conflicts and aggravation of social tension in society. In the work, an analysis was carried out on the example of two separate indicators of the material and living conditions of the whole population of Slovakia for the period of 2005-2020. Selected time series models were used to provide forecast values for the period of 2022-2023. The developed models will allow to provide more reasonable analysis of the effectiveness of social programs and to improve the material and living conditions of the population of Slovakia, to identify target groups of the population that need more support and social assistance.